Devir-tubo Linhas,traços e marcas de uma tese-diagrama na Vila Princesa em Porto Velho-Rondônia - Costa, Thaís Thaianara Oliveira da (2024)
This thesis is carried out as a diving-writing that displaces the thinking process in order to generate a research that surfs between the folds, the smell, the colors, the touch, the images and the contact with art, education and artistic experience as a way to investigate the journey of an artist-teacher, mother and researcher. The writing process is based on the work of writers such as Gilles Deleuze and Félix Guattari (1975), Deleuze and Parnet (1988) Deleuze (1991, 1992, 2003a, 2003b, 2007, 2010 and 2018), Daniel Lins (2008, 2011a and 2011b), authors who approach the fields of art and philosophies of difference. In this work, I propose a “ writing-diving ” as a research method, forged from the writings of Lins (2008) with the text 'Deleuze, the surfer of immanence '. In this becoming-tube, the following questions are placed as an initial problem: what gestures emerge from research in education crossed by the calm and thunder of research in art? How to intertwine the lines of intensity of research, teaching and the body crossed by educational experiences? The method chosen for this thesis-diagram is a diving-writing, tensioned from Deleuze ' s encounter with the surfers. The goal is to operate between the lines and marks of a catastrophe-work and the manual chaos of artistic and teaching production in the midst of a diagram thesis, with small dives into a life permeated by art and teaching in the public education network. The encounters intertwined in this thesis are breath words (Lins, 2008), forged by events in the aesthetics of sliding, a dive into concerns, experiments, compositions and production of images with a movement that brings together the community with its ways of life and creation with students, teacher and researcher.